Phosphodiesterase 5 inhibitor treatment and survival in interstitial lung disease pulmonary hypertension: A Bayesian retrospective observational cohort study. Issue 3 (29th September 2022) - Dawes, Timothy J. W.; McCabe, Colm; Dimopoulos, Konstantinos; Stewart, Iain; Bax, Simon; Harries, Carl; Samaranayake, Chinthaka B.; Kempny, Aleksander; Molyneaux, Philip L.; Seitler, Samuel; Semple, Thomas; Li, Wei; et al.
Abstract: Background and Objective: Pulmonary hypertension is a life‐limiting complication of interstitial lung disease (ILD‐PH). We investigated whether treatment with phosphodiesterase 5 inhibitors (PDE5i) in patients with ILD‐PH was associated with improved survival. Methods: Consecutive incident patients with ILD‐PH and right heart catheterisation, echocardiography and spirometry data were followed from diagnosis to death, transplantation or censoring with all follow‐up and survival data modelled by Bayesian methods. Results: The diagnoses in 128 patients were idiopathic pulmonary fibrosis ( n = 74, 58%), hypersensitivity pneumonitis ( n = 17, 13%), non‐specific interstitial pneumonia ( n = 12, 9%), undifferentiated ILD ( n = 8, 6%) and other lung diseases ( n = 17, 13%). Final outcomes were death ( n = 106, 83%), transplantation ( n = 9, 7%) and censoring ( n = 13, 10%). Patients treated with PDE5i ( n = 50, 39%) had higher mean pulmonary artery pressure (median 38 mm Hg [interquartile range, IQR: 34, 43] vs. 35 mm Hg [IQR: 31, 38], p = 0.07) and percentage predicted forced vital capacity (FVC; median 57% [IQR: 51, 73] vs. 52% [IQR: 45, 66], p= 0.08) though differences did not reach significance. Patients treated with PDE5i survived longer than untreated patients (median 2.18 years [95% CI: 1.43, 3.04] vs. 0.94 years [0.69, 1.51], p = 0.003) independent of all other prognostic markers by Bayesian joint‐modelling (HR 0.39, 95% CI: 0.23, 0.59, p < 0.001) and propensity‐matched analyses (HR 0.38, 95% CI: 0.22, 0.58, p < 0.001). Survival difference with treatment was significantly larger if right ventricular function was normal, rather than abnormal, at presentation (+2.55 years, 95% CI: −0.03, +3.97 vs. +0.98 years, 95% CI: +0.47, +2.00, p = 0.04). Conclusion: PDE5i treatment in ILD‐PH should be investigated by a prospective randomized trial. Abstract : Retrospective cohort data from well phenotyped patients suggests that treatment with a phosphodiesterase 5 inhibitor (PDE5i) is associated with improved survival in patients with interstitial lung disease and severe pulmonary hypertension (ILD‐PH), particularly in those with normal right ventricular function at presentation. A randomized controlled trial of pulmonary vasodilator therapy in ILD‐PH is warranted. See related Editorial